Cross-Modal Supervision Based Road Segmentation and Trajectory Prediction with Automotive Radar - Wang, Zhaoze; Jin, Yi; Deligiannis, Anastasios; Fuentes-Michel, Juan-Carlos; Vossiek, Martin (IEEE Robotics and Automation Letters, 2024)
Automotive radar plays a crucial role in providing reliable environmental perception for autonomous driving, particularly in challenging conditions such as high speeds and bad weather. In this domain the deep learning-based method is one of the most promising approaches, but the presence of noisy signals and the complexity of data annotation limit its development. In this paper, we propose a novel approach to address road area segmentation and driving trajectory prediction tasks by introducing Differential Global Positioning System (DGPS) data to generate labels in a cross-modal supervised manner. Then our method employs a multi-task learning-based CNN trained by radar point clouds or occupancy grid maps without any manual modification. This multi-task network not only boosts processing efficiency but also enhances the performances in both tasks, compared with single-task counterparts. Experimental results on a real-world dataset demonstrate the effect of our implementation qualitatively, achieving decimeter-level predictions within a 100 m forward range. Our approach attains an impressive 91.4 % mean Intersection over Union (mIoU) in road area segmentation and exhibits an overall average curve deviation of less than 0.35 m within a range of 100 m forward in trajectory prediction. The source code is available at https://wangzhaoze.github.io/RADxGPS/ .<br
Keywords: Radar; Trajectory; Task analysis; Roads; Point cloud compression; Spaceborne radar; Global Positioning System; Intelligent transportation systems; semantic scene understanding; automotive radar; cross-modal learning